Biochar enhances soil interactions and the initial development of sugarcane - Ferreira, Osania Emerenciano; Silva, Halax Duart Martins; Alves, Adriana Barboza; de Aguilar, Mariana Guerra; Pimenta, Lúcia Pinheiro Santos; Costa, Gustavo Henrique Gravatim; da Cruz, Mara Cristina Pessôa [UNESP]; da Silva Bezerra, Augusto Cesar; Machado, Alan Rodrigues Teixeira (Springer Nature, 2024)
The present study evaluated the effects of biochar derived from sugarcane straw on the physicochemical and biological properties of soil and the initial development of sugarcane. Microcosm and pot experiments were conducted over 60 days to monitor variables such as pH, water retention capacity, microbial activity, initial growth, and the metabolomic profile of the plant leaves. The results indicated that biochar increased the soil water retention capacity without significantly affecting the pH. The biochar significantly promoted root length and mass and favored the growth of the soil microbiota, as reflected by an increase in the amount of microbial biomass carbon. Metabolomic analysis of sugarcane leaves revealed that soil conditioning with biochar at application rates of 3 and 5% w/w led to increased concentrations of the amino acids isoleucine and valine, accompanied by a reduction in galactose, maltose, and glucose levels. Furthermore, biochar treatment resulted in a decrease in aconitic acid and an increase in acetic and succinic acid concentrations. These findings suggest that biochar may be a promising strategy for enhancing the productivity and sustainability of sugarcane cultivation.
Keywords: Biomass; Carbon; Metabolome; Microbiota; NMR